2019
DOI: 10.5005/jp-journals-10054-0094
|View full text |Cite
|
Sign up to set email alerts
|

Cost Analysis in the Clinical Chemistry Laboratory in the Era of Automation: Our Experience

Abstract: Aim: In the era of automation, the modalities available for analysis of samples for a clinical chemistry laboratory include both wet chemistry and dry chemistry analyzers. Wet chemistry systems are routinely used in small to large clinical chemistry laboratories whereas dry chemistry analyzers are restricted to large laboratories. Cost analysis is a system that is used for providing financial information to make financial projections. Aim of the study was to compare the cost analysis of wet chemistry and a dry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…However, when considering high specific workloads, the cost per reporting test (CPRT) of the dry chemistry system was found to be lower than that of the wet chemistry system. 5 Beside the cost factor, dry chemistry analyzer is also believed to enhance performance in external quality assurance schemes (EQAS) as observed by Mukherjee et al 12 The high level of correlation and agreement observed suggests that both systems can provide reliable results. However, it is important to consider the specific parameters and limitations of each system when interpreting the results.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, when considering high specific workloads, the cost per reporting test (CPRT) of the dry chemistry system was found to be lower than that of the wet chemistry system. 5 Beside the cost factor, dry chemistry analyzer is also believed to enhance performance in external quality assurance schemes (EQAS) as observed by Mukherjee et al 12 The high level of correlation and agreement observed suggests that both systems can provide reliable results. However, it is important to consider the specific parameters and limitations of each system when interpreting the results.…”
Section: Discussionmentioning
confidence: 95%
“…Tests run on wet chemistry analyzers generally have a lower cost compared to those run on dry chemistry analyzers. 5 Currently, we are running both these system side by side in the Department of clinical biochemistry of Dhulikhel Hospital. The present study intends to compare the agreement of results between dry and wet chemistry systems for common clinical chemistry parameters i.e., Glucose, urea, creatinine, total bilirubin, total protein, albumin, total calcium, total cholesterol, triglyceride, HDL-Cholesterol, AST and ALT respectively.…”
Section: Methodsmentioning
confidence: 99%